2001
DOI: 10.1101/gad.907201
|View full text |Cite
|
Sign up to set email alerts
|

The yeast SAS (something about silencing) protein complex contains a MYST-type putative acetyltransferase and functions with chromatin assembly factor ASF1

Abstract: It is well established that acetylation of histone and nonhistone proteins is intimately linked to transcriptional activation. However, loss of acetyltransferase activity has also been shown to cause silencing defects, implicating acetylation in gene silencing. The something about silencing (Sas) 2 protein of Saccharomyces cerevisiae, a member of the MYST (MOZ, Ybf2/Sas3, Sas2, and TIP60) acetyltransferase family, promotes silencing at HML and telomeres. Here we identify a ∼450-kD SAS complex containing Sas2p,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
130
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(135 citation statements)
references
References 54 publications
3
130
0
Order By: Relevance
“…5). In yeast, it was also demonstrated that Asf1 interacts with a SAS complex, which is a member of the MYST acetyltransferase family (Osada et al, 2001). In this species, the SAS complex promotes silencing at telomeres, providing evidence for an important role of the acetyltransferase activity of the SAS complex in silencing.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…5). In yeast, it was also demonstrated that Asf1 interacts with a SAS complex, which is a member of the MYST acetyltransferase family (Osada et al, 2001). In this species, the SAS complex promotes silencing at telomeres, providing evidence for an important role of the acetyltransferase activity of the SAS complex in silencing.…”
Section: Discussionmentioning
confidence: 96%
“…In this species, the SAS complex promotes silencing at telomeres, providing evidence for an important role of the acetyltransferase activity of the SAS complex in silencing. Even more, yeast asf1 mutants show silencing defects similar to mutants in the SAS complex (Osada et al, 2001). Thus, Asf1-dependent chromatin assembly may mediate the silencing role of the SAS complex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SAS complex can acetylate the N-terminal tails of free histones H3 and H4; although somewhat surprisingly, the SAS complex cannot acetylate histones bound to Asf1 (28). Although the HAT for acetylation of soluble Lys-56 is unknown, the SAS complex is an unlikely candidate because inactivation of this complex does not cause sensitivity to DNA damaging agents (27) as is the case for yeast unable to acetylate H3 Lys-56 (15).…”
Section: Asf1 Is Likely To Present the Newly Synthesized Freementioning
confidence: 99%
“…4C). The only HAT known to associate with Asf1 to date is the SAS complex, composed of Sas2, Sas4, and Sas5 (27). The SAS complex can acetylate the N-terminal tails of free histones H3 and H4; although somewhat surprisingly, the SAS complex cannot acetylate histones bound to Asf1 (28).…”
Section: Asf1 Is Likely To Present the Newly Synthesized Freementioning
confidence: 99%